Penggunaan Steroid Sebagai Pengobatan Preventif untuk Transient Facial Nerve Palsy pada Parotidektomi - Adham, Marlinda; Windri, Sellina; Agung, Ibrahim (Oto Rhino Laryngologica Indonesiana, 2024)
Background and Objective: One of the most reported complication of parotidectomy or other parotid surgery is facial nerve palsy. Steroids such as glucocorticoid have been known to help preserve nerve damage. But there’s lack of evidence that shows the use of steroids to help nerve recovery. So authors are determined to find the association between steroid intervention in parotidectomy patients to prevent or to help accelerate recovery rate in facial nerve palsy cases. Methods: This evidence-based case report used the PICO method for literature search in two databases (Ovid and PubMed). After selecting the article using inclusion and exclusion criteria, the author appraised the article using the Center of Evidence Based Medicine (CEBM) Oxford Appraisal Tools. Results: In total of 2 articles we found, we include all of them for analysis. Both of the articles shows that there’s no correlation between giving steroids to post-parotidectomy patients and faster recovery rate. In contrary, one study shows that placebo-treated groups had a faster facial nerve function recovery rate than steroid-treated patients. Conclusion: Giving steroids to post-parotidectomy patient won’t help accelerate the facial nerve function recovery rate. Prevention of facial nerve palsy in parotidectomy was preferred as treatment.